PENGARUH INDEKS PEMBANGUNAN MANUSIA TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN BULUKUMBA - B, Aulia Rahman (ICOR: Journal of Regional Economics, 2021)
This study aims to determine the effect of the health index, education index and purchasing power index simultaneously on economic growth in Bulukumba Regency. This study is quantitative research, while the analytical data method used is the statistical method and multiple linear analysis. Data used is secondary data originating from historical records or reports that are arranged in published archives and which are not published. The results of this study indicate that the health index, education index and purchasing power index have a significant effect on economic growth in Bulukumba Regency. This research is expected to be a reference for the government to take the right and good solutions to use in solving problems related to economic growth in Bulukumba Regency. Keywords: Economic growth, health index, education index, purchasing power parity.